Bis[(2S,4S)-4-(2-hydroxyethyl)-2-methylpiperazine-1,4-diium] di-μ-chlorido-bis[trichloridocadmium(II)] - Rong, Tao (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, (C(7)H(18)N(2)O)(2)[Cd(2)Cl(8)], comprises one 4-(2-hydroxyethyl)-2-methylpiperazine-1,4-diium dication and a half [Cd(2)Cl(8)](4−) anion. The two Cd atoms are each coordinated by two bridging Cl atoms and three terminal Cl atoms and the [Cd(2)Cl(8)](4−) anion is located on an inversion centre. The crystal structure consists of N—H⋯Cl hydrogen-bonded sheets, which are further linked by C—H⋯Cl contacts, yielding a three-dimensional network.